2018
DOI: 10.18632/oncotarget.25420
|View full text |Cite
|
Sign up to set email alerts
|

Comparative molecular characterization of typical and exceptional responders in glioblastoma

Abstract: Glioblastoma (GBM) is the most common and the deadliest type of primary brain tumor, with a median survival time of only 15 months despite aggressive treatment. Although most patients have an extremely poor prognosis, a relatively small number of patients survive far beyond the median survival time. Investigation of these exceptional responders has sparked a great deal of interest and is becoming an important focus in the field of cancer research. To investigate the molecular differences between typical and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…GBM is characterized by rapid progression and invasion, cell infiltration, intense angiogenesis, resistance to radio- and chemotherapies, and high frequency of relapse. This aggressive behaviour is responsible for the poor prognosis, with a median survival of about 14 months and a 5-year survival rate of 5.1% [ 1 ]. GBM resistance to therapies and the high frequency of recurrence are mainly due to a subpopulation of tumourigenic stem-like cells, known as GBM stem cells (GSCs), able to hierarchically initiate, maintain, and spread the neoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…GBM is characterized by rapid progression and invasion, cell infiltration, intense angiogenesis, resistance to radio- and chemotherapies, and high frequency of relapse. This aggressive behaviour is responsible for the poor prognosis, with a median survival of about 14 months and a 5-year survival rate of 5.1% [ 1 ]. GBM resistance to therapies and the high frequency of recurrence are mainly due to a subpopulation of tumourigenic stem-like cells, known as GBM stem cells (GSCs), able to hierarchically initiate, maintain, and spread the neoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Further molecular analyses demonstrated a deletion of cyclin-dependent kinase inhibitor 2A (CDKN2A). In this patient, a CDKN2A deletion was detected, which is associated with shortened survival and limited response to radiation therapy in patients with GBM (13,14). Resistance to TTFields therapy was assumed in a prior reported case with this constellation of characteristics (15), but TTFields resistance was not evident in this case study.…”
Section: Discussionmentioning
confidence: 62%
“…FLG is a high-affinity receptor of basic fibroblast growth factor (bFGF), and a recent report by Wipfler et al has shown that FLG has a significantly different distribution of patients affected by somatic nonsynonymous mutations. Of these, 25% of exceptional responders had one mutation each in FLG [13]. In contrast, overexpression of FLG is associated with low immune cell infiltration and short survival rates in melanoma and ovarian cancer [55], while the loss of function mutations in FLG is associated with lower cancer risk in several cancers [56].…”
Section: Gene Mutation Frequency Within Survival Classesmentioning
confidence: 99%
“…Thus, we feel that in addition to the classification of brain tumours that have been done so far, it is also equally important to stratify brain cancer patients based on their survival characteristics and which will permit us to clinicians to tailor both the timing and the type of treatments to patients [12,13]. This will, for example, be helpful or avoid overtreating those patients with more stable disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation